Immigration, integration, and citizenship policies in Portugal: The case of health in the 21st century - Asensio, M.; Padilla, B. (Studies in Health Sciences, 2021)
This article investigates to what extent immigration is confronting the Welfare States with citizenship limitations as citizenship has been called into question by immigration, globalization, and the increasing internal debate of political communities. This case study of immigration in Portugal examines the contradiction between the rhetoric of immigrant integration portrayed by the State and the reality of immigrant exclusion. Existing research highlights the importance of international human rights frameworks as a catalyst for governments’ recognition of immigrants’ social rights. The study of Portuguese immigration policy on which this article is based was undertaken as a way to explore such apparent contradictions. As a Southern European country that has undergone an enormous political and economic transformation in the last three decades, experiencing the contradictions of advanced capitalist societies in an intensified way, Portugal offers an interesting case study for such analysis. This article aims to fill this gap. As we will see, the health policy on immigrants in Portugal can illuminate not only the contradictions of Portuguese society but also the broader contradictions of the Welfare State in the new global economy.